1984
DOI: 10.1111/j.1651-2227.1984.tb09988.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Idiopathic Nephrotic Syndrome with Levamisole

Abstract: Thirty children with frequently relapsing idiopathic nephrotic syndrome (INS) were treated with levamisole (2.5 mg/kg BW) twice a week for a mean period of 9.9 months. A beneficial effect was observed in 16 children in whom corticosteroids could be significantly decreased without relapse. Levamisole was ineffective in 14 patients. There was no difference between the two groups in the duration of INS, the number of relapses and the duration of treatment with levamisole. The mean age at onset of INS was higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 8 publications
(2 reference statements)
1
22
0
Order By: Relevance
“…It is a randomized controlled clinical trial, using Ievamisole as the sole drug in the treatment group, keeping in mind the following facts, viz (a) initial remission is easily induced with corticosteroids with minimal side-effects [15], (b) relapses occurring in the first 6 months after attaining remission very often herald multiple subsequent relapses [17], (c) relapses are directly related to depression of T-cell function [7], (d) Ievamisole is known to restore T-cell function [10], (e) the responses obtained in most studies with Ievamisole were directed at inducing remission and not at maintaining remission [9,11], and (0 most studies recruited only multiple relapsers [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a randomized controlled clinical trial, using Ievamisole as the sole drug in the treatment group, keeping in mind the following facts, viz (a) initial remission is easily induced with corticosteroids with minimal side-effects [15], (b) relapses occurring in the first 6 months after attaining remission very often herald multiple subsequent relapses [17], (c) relapses are directly related to depression of T-cell function [7], (d) Ievamisole is known to restore T-cell function [10], (e) the responses obtained in most studies with Ievamisole were directed at inducing remission and not at maintaining remission [9,11], and (0 most studies recruited only multiple relapsers [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…It influences host defences by norma lizing the lowered cell-mediated immune response. There have been several studies demonstrating the use of levami sole in MCNS [7,[9][10][11][12][13][14], However, only 2 of these were controlled trials and the follow-up period was limited.…”
Section: Introductionmentioning
confidence: 99%
“…Levamisole has thus been used to boost the immune system of patients suffering diseases that were supposed to be associated with, or that received treatments leading to, decreased immunity. Hence levamisole has been used for the treatment of rheumatoid arthritis (Schuermans 1975), of pediatric nephrotic syndrome (Tanphaichitr et al 1980;Niaudet et al 1984;Mongeau et al 1988; British Association for Paediatric Nephrology 1991) and against various skin infections (reviewed in Hadden et al 1977). Nevertheless, more recent studies have somehow questioned the efficacy of levamisole as an immunostimulant (e.g.…”
Section: Side Effects Of Tetramisole and Levamisole Therapiesmentioning
confidence: 97%
“…Since Tanpaichitr et al [49] first de scribed the efficacy of the T-cell-stimulating agent, levamisole, in nephrotic syndrome in 1980, several reports [50,51] have confirmed that the medication is useful, albeit less effective than was stated in the original studies. The usual oral dose (1.5-4 mg/kg twice weekly) is doubled for initial nonresponders [50], The duration of treatment varies considerably, between 1 and 18 months. Remission rates of 60-100% have been achieved, but fewer than 100 patients have been reported [49][50][51], The only side effect seems to be dose-dependent neutropenia.…”
Section: Noncorticosteroid Treatmentsmentioning
confidence: 99%
“…The usual oral dose (1.5-4 mg/kg twice weekly) is doubled for initial nonresponders [50], The duration of treatment varies considerably, between 1 and 18 months. Remission rates of 60-100% have been achieved, but fewer than 100 patients have been reported [49][50][51], The only side effect seems to be dose-dependent neutropenia. Among 3,900 oncologic and rheumatologic patients [52] who were treated with levamisole, the prevalence of neutropenia was 2.3%, and was reversible in all patients after cessation of treatment.…”
Section: Noncorticosteroid Treatmentsmentioning
confidence: 99%